Heat stress during seed development affects forage brassica (Brassica napus L.) seed quality. (23rd November 2017) - Rashid, M.; Hampton, J. G.; Rolston, M. P.; Khan, K. M.; Saville, D. J.
Abstract: In two consecutive seasons, forage rape ( Brassica napus L.) plants were exposed to short periods (240°C hr) of heat stress (30°C day/25°C night) during seed filling (80% seed moisture content = S1), at physiological maturity (50% seed moisture content = S2) and at both S1 plus S2 (=S3) in a Biotron before being returned to the field until seed harvest. Seeds were hand harvested at 14% seed moisture content and their quality assessed by measuring germination, seed vigour (using the accelerated ageing and conductivity tests) and seed mass (as determined by thousand seed weight). Heat stress at both S1 and S2 caused a small (<10%) but significant reduction in germination in both seasons. There was a significant heat stress timing interaction in the first but not the second season. Reductions in germination were a result of increased abnormal seedling production not seed death. All three heat stress treatments significantly reduced seed vigour, with S3>S2>S1. Seed mass was reduced by heat stress at S1 but not at S2. Variable seed vigour in high‐germinating New Zealand‐produced forage rapeseed lots is most likely explained by short periods of heat stress during seed development.